The Effect of Project-Based Learning Using E-Learning on Student Learning Outcomes in Vocational Education Courses - Desmira Desmira; Muhammad Sonhaji Akbar; Erik Rahman; Taufik Taufik; Julius Jonas Mbawala (Vocational: Journal of Educational Technology, 2026)
The integration of digital technology in higher education has accelerated the need for innovative pedagogical approaches that foster active learning and digital competence. Project-Based Learning (PjBL) supported by e-learning provides authentic, technology-driven experiences that are particularly valuable in vocational education, where students must connect theory with practice. This study examined the effect of PjBL using e-learning on student learning outcomes in vocational education courses at the Department of Information Technology Education, Universitas Negeri Surabaya. A quasi-experimental pretest–posttest control group design was employed with 64 purposively selected undergraduate students from the 2024/2025 academic cohort. Participants were assigned equally to an experimental group (n = 32), which received PjBL integrated with e-learning, and a control group (n = 32), which received conventional lecture-based instruction. Data were collected through pretests and posttests and analyzed using descriptive statistics, independent samples t-test, and effect size calculations. Findings revealed that the experimental group achieved significantly higher posttest scores (M = 84.63, SD = 5.21) compared to the control group (M = 76.88, SD = 6.02). The independent samples t-test confirmed the significance of the difference (t = 5.67, p < 0.001), while Cohen’s d (d = 1.32) indicated a large effect size. These results demonstrate that integrating PjBL with e-learning substantially improves learning outcomes in vocational education. In conclusion, PjBL supported by e-learning offers an effective instructional strategy for enhancing problem-solving, higher-order thinking, and active student engagement. The findings suggest that aligning pedagogy with digital platforms can optimize learning effectiveness and strengthen students’ readiness for professional challenges.